Forest policy priorities: Forest Management Comparative Analysis (Russia, Canada, Brazil and USA) - NOSOVA, Svetlana Sergeevna; ABDULOV, Rafael Envarovich; MEDVEDEVA, Yulia Mihailovna; SHIRYAEV, Dmitry Valentinovich; KAMENSKIKH, Nadezhda Alekseevna (Journal of Environmental Management and Tourism, 2016)
This article studies current forest management system in Russia and identifies forest policy priority areas which can make forestry sector more effective. The author puts forward a new method of quantitative effectiveness assessment for forest management comparing the Russian forestry to the other forest-rich countries (Canada, Brazil and the USA). The national forestry sector growth has been nurtured by the world largest forest reserves. Production forest land in Russia is 22.7 times and 4.5 times larger than Canada or the USA respectively. Having the largest forest land areas with management plan Russia however lags behind Canada in sustainable forest management which is the global leader in forest certification. The research outcomes show that Russia has not made yet full use of its economic capacities in forestry sector. Compared to the other world’s forest-richest countries, forestry sector in Russia remains economically low effective. More rational distribution of powers between federal, regional and community levels as well as transition to the intensive model of use of national resources may contribute to more effective and competitive forestry sector of the Russian economy. To make Russian business more competitive on the export markets we need to promote and facilitate facultative certification by granting fiscal benefits, i.e. tariff and tax facilitations, to certified companies.
Keywords: forest management; forestry; forest resources; reforestation; forest policy